2020
DOI: 10.3390/atmos11121340
|View full text |Cite
|
Sign up to set email alerts
|

Meteorological Factors Controlling 7Be Activity Concentrations in the Atmospheric Surface Layer in Northern Spain

Abstract: This work presents the analysis of weekly 7Be activity concentrations in the air measured in Bilbao (northern Spain) by collecting aerosols in filters over a ten years period (2009–2018). 7Be level is in the 0.35–7.3 mBq/m3 range, with a mean of 3.20 ± 1.12 mBq/m3. The trend, cycle, seasonal and monthly variability are evaluated using time series analysis techniques. The results indicate the impact of sunspots (24th solar cycle) on interannual 7Be activity concentrations, and a significant seasonal and monthly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 49 publications
0
7
1
Order By: Relevance
“…The minimum value (P5) increases from 107 µBq/m 3 to 224 µBq/m 3 , while the maximum value (P95) ranges from 803 µBq/m 3 to 1315 µBq/m 3 . The occurrence of the maximum in autumn is not in line with previous works analyzing beta activity concentrations conducted in the Iberian Peninsula [16][17][18], which showed that the maximum average values are reached in the summer and that the minimum values are obtained in the winter. On the contrary, similar behaviour has been found in other analyses, such as in Milan [27] and New York [28].…”
Section: Beta Activity Concentrationscontrasting
confidence: 67%
See 2 more Smart Citations
“…The minimum value (P5) increases from 107 µBq/m 3 to 224 µBq/m 3 , while the maximum value (P95) ranges from 803 µBq/m 3 to 1315 µBq/m 3 . The occurrence of the maximum in autumn is not in line with previous works analyzing beta activity concentrations conducted in the Iberian Peninsula [16][17][18], which showed that the maximum average values are reached in the summer and that the minimum values are obtained in the winter. On the contrary, similar behaviour has been found in other analyses, such as in Milan [27] and New York [28].…”
Section: Beta Activity Concentrationscontrasting
confidence: 67%
“…On the same roof where the low air sampler was located, there was also a high flow sampler. From 2001 to 2018, during two periods of time (2001-2008 and 2009-2018), the 7 Be concentration had been analysed [14,15,17,18].…”
Section: Beta Activity Concentrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the studied period (2017-2018), temperature averages between 11 • C in winter and 21 • C in summer, while annual precipitation averages over 830 mm, with a yearly average of 142 days with at least 1 mm. Previous analysis [21] has demonstrated that this area is typically affected by air masses from the northwest, west, north, northeast, and south, which are combined in spring and summer with the development of mesoscale circulations in surface levels, i.e., sea-land breezes.…”
Section: Study Areamentioning
confidence: 98%
“…Atmospheric 7 Be near ground level generally seems to be originated from the upper troposphere, due to its relatively short physical half-life (53.3 days) and long removal time (1–2 years) in the stratosphere [ 6 ]. The following factors are known to produce the (seasonal) fluctuations in 7 Be activity concentration levels at ground level [ 7 , 8 , 9 ]: cosmic-ray intensity [ 10 , 11 ], the exchange of atmosphere between the troposphere and stratosphere [ 12 , 13 ], the north–south or east–west mixing of atmosphere [ 14 ], and the frequency of precipitation [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%